Repair of Bimalleolar Ankle Fracture. (August 2017) - Fisher, Nina; Atanda, Abiola; Swensen, Stephanie; Egol, Kenneth A.
Abstract : Purpose: The incidence of ankle fractures is rapidly increasing in geriatric populations. Of the 4 fracture patterns described by the Lauge-Hansen classification system, supination-external rotation (SER) accounts for most ankle fractures. This video demonstrates surgical repair of a SER type 4 ankle fracture in a geriatric patient. Methods: SER type 4 ankle fractures are considered unstable and are generally treated with surgical fixation. After placement of plate and screws, intraoperative stress tests can be used to assess for syndesmotic widening. If necessary, the syndesmosis can be reduced open, with screw fixation placed parallel to the joint. Patients are kept non–weight-bearing for 6 weeks after surgery. Results: This video, shot on an iPhone 6S, shows the case of a 66-year-old female status after a fall with twisting mechanism resulting in an unstable SER type 4 fracture requiring operative repair. Intraoperative stress test revealed medial clear space widening requiring syndesmotic reduction. Conclusions: SER type 4 ankle fractures are a common injury that must be properly managed to return patients to baseline functional status. The surgical technique described in this video provides for good stabilization and allows for early range of motion with advancement to weight-bearing as tolerated at 6 weeks postoperatively.